Sistem Informasi Keuangan Pada Pt Total Lintas Samudera - Willdahlia, Ayu Gede (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2021)
PT Total Lintas Samudera is a company engaged in Logistics & domestic and international shipping services. At PT Total Lintas Samudera, reports are still made separately between the customer service and accounting divisions with a single entry or made per division and are not connected in one system. Between expenditure data and financial reports have not been connected in one system, which causes it to be unable to generate reports automatically. This makes the company work less effectively and efficiently, which results in the slow preparation of reports. For this reason, an information system is designed and built to manage web-based financial reports to make it easier to present reports more efficiently—design and Build of Financial Information System PT. Total Ocean Crossing begins with collecting data, and then from that data, functional and non-functional analysis can be carried out. After that, do the design, prepare black box testing test scenarios, determine the schedule of activities, implement the system, and finally do system testing—financial Information System PT. Total Lintas Samudera has two user levels, namely admin and leadership. The test results found that the test was by the system design, and everything could work as expected.